Monuments et mémoires publiés par l'Académie des inscriptions et belles-lettres - Académie des inscriptions & belles-lettres (France); Fondation Eugène Piot (E. Leroux, 1894)
Biographical sketch of Eugène Piot by Georges Perrot in v. 1, p. [vii]-xxiii, with portrait in text.
Keywords: Art : Periodicals; Art : Associations; Art